Nature of Human Rights Violation on Female Garments Workers in Bangladesh - MD. Basirulla; Farhat Tasnim (Khazanah Hukum, 2023)
Bangladesh, a fast-growing developing country, has been experiencing rapid development in export-oriented industrialization. The total contribution of the garment industries to the national foreign exchange earnings is around 83%. About 80% of garment workers are women, and most have migrated from rural areas to industrial cities. Female workers have been an important factor in the growth of the garment industry in Bangladesh. Despite its contribution to the national economy and employment opportunities, the garment industry in Bangladesh is beset by many grievances. Such as sexual harassment, health problems, lack of toilet facilities, exploitation of low-paid and overworked workers and large-scale social insecurity. The present research analyzed such violations from different aspects with a qualitative approach, The main objective of this paper is to find out the types and nature of human rights violations that occur against female garment workers in Bangladesh. The present research combines both exploratory and descriptive methods. Sampled garment workers from two selected factories were surveyed and interviewed to understand the practical situation at the field level. The data findings have provided a complete picture of the nature of the human rights violations that occurred. The human rights of women workers have been found to be violated from all nine indicators. The patriarchal socio-economic setting and economic vulnerability of the women and their lack of awareness, as well as reluctance and quick profit motive of the factory owners, have contributed most to such unwanted situations.